Evaluation in Advertising Reception : A Socio-Cognitive and Linguistic Perspective - Bullo, Stella; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Placed within the context of reception studies, this book investigates how advertisements that rely on re-contextualising shared cultural knowledge are understood by their viewers, and examines their persuasive potential.
Keywords: Social sciences; Marketing; Sociolinguistics; Discourse analysis; Communication; Sociology; Mass media